Landscape change and Land-use/Land-Cover Dynamics in Rondônia, Brazilian Amazon. - BATISTELLA, M. (2001)
Motivations for the study of landscape change in Rondônia, Brazilian Amazon; Environmental and cultural setting the opportunity for a comparative study; Vegetation structure as an indicator for Land-cover dynamics assessment in the Amazon; Lulc dynamics: the colonization impact; Landscape change described by selected metrics; Beyond the metrics: human dimensions of landscape change; Concluding remarks.